P2-S6.08 Examining risk in high risk "populations: measuring sexual behaviour among men who have sex with men". (10th July 2011) - Rosenberger, J G; Reece, M; Novak, D S; Herbenick, D; Fortenberry, J D; Van Der Pol, B
Abstract : Purpose: Due to the disproportionate impact of HIV and other sexually transmitted infections (STIs) on men who have sex with men (MSM), men who indicate same gendered sexual interactions are categorised as a priority population and often perceived as high-risk". While acknowledging the potential for increased risk among certain populations is important for disease prevention and transmission efforts, this approach broadly labels men based on a limited behavioural profile without consideration for the contextual factors of a given sexual event that influence potential disease exposure. This study sought to assess sexual behaviour among MSM in the USA during their most recent sexual event and identify factors associated with decreased risk for HIV/STI. Methods: Data were collected via an internet survey from 27, 690 18–80-year old MSM. Measures included sociodemographics, recent/lifetime sexual behaviour history, and sexual experience items. Results: Participants' median age was 39.0 years, ethnicities included white (84.5%), Latino (6.4%), African American (3.5%), and most (79.9%) identified as homosexual. Most participants reported a sexual event within the past month (86.1%), with the majority indicating their most recent event in the past 7 days (60.1%). While most men reported not engaging in insertive (35.2%) or receptive (37.0%) anal intercourse, of those who did, 46.1% used a condom and almost none reported ejaculation occurring in their or their partner's anus, 2.7% and 2.5% respectively. Among men (24.5%) who described their sexual partner as a boyfriend or spouse, nearly half reported they and their partner had not had other sexual partners during the past 6 months (44.7%), and the majority had been tested for STIs (61.6%) and HIV (64.8%). Conclusions: These data provide a large scale assessment of sexual behaviour during the most recent sexual event among MSM in the USA. Findings from this study highlight diversity in behaviours and demonstrate varying degrees of potential risk for HIV and other STIs, regardless of gender. Future prevention efforts should consider contextual components of sexual events, including partner type, HIV and STI testing patterns, and semen exposure, to more accurately develop custom risk reduction strategies.